The handbook for quality management : a complete guide to operational excellence - Pyzdek, Thomas; Keller, Paul (New York : McGraw Hill Education, 2013)
The Handbook for Quality Management: A Complete Guide to Operational Excellence, Second Edition offers in-depth guidance on effectively applying the principles of quality management in today's business environment and delivering superior results. Written by two of the foremost authorities on the subject and fully updated for the latest American Society for Quality (ASQ) Certified Manager of Quality/Organizational Excellence (CMQ/OE) Body of Knowledge, The Handbook for Quality Management, Second Edition provides an operational guide to the proper understanding and application of quality management in the current business environment. It serves as a primary reference source for an organization's quality program and for anyone seeking to pass the CMQ/OE exam, given by the ASQ, and also serves as an essential on-the-job reference.
Part I. Business-Integrated Quality System -- Part II. Integrated Planning -- Part III. Process Control -- Part IV. Continuous Improvements -- Part V. Management of Human Resources .
Includes bibliographical references and index.
Keywords: MANAGEMENT HANDBOOKS